Picasso, Dalí or Frida had Social Media? Life as a Spectacle or an Antecedent for Modern Construction of Virtual Subjectivities - González Torres, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
They were not users of Facebook, Twitter and Instagram; neither bloggers, youtubers or influencers. Pablo Picasso, Salvador Dalí y Frida Kahlo did not know the multiple functions of networked technologies. However, their lives as creative artists and imbued with an unprecedented media spectacular, are a notable source of iconic influence. The numerous photographs that the three of them carried out are a singular antecedent so that today, decades in between and through social networks, contemporary users construct their own virtual subjectivities taking them as models.